Cloud Computing and Digital Media - Li, Kuan-Ching; Li, Qing; Shih, Timothy (Chapman and Hall/CRC, 2014)
Cloud Computing and Digital Media: Fundamentals, Techniques, and Applications presents the fundamentals of cloud and media infrastructure, novel technologies that integrate digital media with cloud computing, and real-world applications that exemplify the potential of cloud computing for next-generation digital media. It brings together technologie.
Online resource; Title from title page (viewed March 7, 2014)
Keywords: Cloud computing; Computer storage devices; Digital communications; Cloud Computing; Computer Storage Devices; Satellite Communications; Infonuagique; Ordinateurs; Mémoires; Transmission numérique